Имплицитные формы предпосылок научного знания - Смоляга, Марина Витальевна; Старикова, Галина Геньевна (НТУ "ХПИ", 2016)
Статья посвящена проблеме предпосылочных компонентов научного знания. Рассматривается история исследования проблемы, особое внимание при этом уделяется постпозитивистским моделям развития науки. В частности, анализируется выдвинутое современными исследователями требование признать равноправным со специально-научным также мировоззренческое предпосылочное знание, обладающее своими собственными формами и средствами. Предпосылочное знание рассматривается также как очевидное, имплицитное знание, которое не поддается вербализации. Проанализирована роль нерефлектируемых, неэксплицируемых философских предпосылок в научном познании.

The article is devoted to the problem of basic unknown components in scientific knowledge. The implicit knowledge was not the theme of serious scientific and philosophy investigation till XX century. Curtesy decided such question in his theory of obvious as a description of scientific knowledge. Also the Kant’s conception of a priory knowledge gave a new point of view to this problem. Butonly in postpositive philosophy the problem of implicit basic knowledge became actuality. K. Popper, I. Lacatos, M.Polani devoted especially attention to such problems. Modern investigators put forward the demand of between the special-scientific and basic knowledge which has it’s own forms, capacity and possibilities. The basic unknown components are believed also as the obvious, implicit knowledge which cannot be verbalization. The role of not reflexing, not explicated philosophy basic knowledge in the scientific knowledge was analyzed.
The implicit forms of basic unknown components in scientific knowledge
Keywords: предпосылочное знание; имплицитное знание; неявное знание; очевидность; философские основания науки; basic knowledge; implicit knowledge; unknown knowledge; obvious; philosophy basis of science